Clinical utility of colonic low‐amplitude propagating contractions in children with functional constipation. Issue 5 (27th February 2023) - Colliard, Kitzia; Patel, Dhiren; Nurko, Samuel; Rodriguez, Leonel
Abstract: Background: Colonic high‐amplitude propagating contractions (HAPC) are generally accepted as a marker of neuromuscular integrity. Little is known about low‐amplitude propagating contractions (LAPCs); we evaluated their clinical utility in children. Methods: Retrospective review of children with functional constipation undergoing low‐resolution colon manometry (CM) recording HAPCs and LAPCs (physiologic or bisacodyl‐induced) in three groups: constipation, antegrade colonic enemas (ACE), and ileostomy. Outcome (therapy response) was compared to LAPCs in all patients and within groups. We evaluated LAPCs as potentially representing failed HAPCs. Key Results: A total of 445 patients were included (median age 9.0 years, 54% female), 73 had LAPCs. We found no association between LAPCs and outcome (all patients, p = 0.121), corroborated by logistic regression and excluding HAPCs. We found an association between physiologic LAPCs and outcome that disappears when excluding HAPCs or controlling with logistic regression. We found no association between outcome and bisacodyl‐induced LAPCs or LAPC propagation. We found an association between LAPCs and outcome only in the constipation group that cancels with logistic regression and excluding HAPCs ( p = 0.026, 0.062, and 0.243, respectively). We found a higher proportion of patients with LAPCs amongst those with absent or abnormally propagated (absent or partially propagated) HAPCs compared to those with fully propagated HAPCs ( p = 0.001 and 0.004, respectively) suggesting LAPCs may represent failed HAPCs. Conclusions/Inferences: LAPCs do not seem to have added clinical significance in pediatric functional constipation; CM interpretation could rely primarily on the presence of HAPCs. LAPCs may represent failed HAPCs. Larger studies are needed to further validate these findings. Abstract : Despite of being separate entity than HAPCs, the clinical utility of LAPCs have not been studied in pediatric motility disorders. The aim of this study was to evaluate the clinical utility of the LAPCs in pediatric patients undergoing manometry for functional constipation. LAPCs were reviewed in detail retrospectively from manometry database. LAPCs do not seem to have added clinical significance over HAPCs in pediatric functional constipation, the interpretation of the CM could rely primarily on the presence and quality of HAPCs. LAPCs are associated with mass movement and passage of flatus and could represent failed HAPCs. Larger studies are needed to further validate these findings.